Rumah Saudagar Batik Laweyan di Surakarta; Bangunan Berarsitektur Hybrid - Rudy Surya; Naniek Widayati P; Alvin (Archvisual: Jurnal Arsitektur dan Perencanaan, 2021)
The Laweyan area has been known since the kingdoms era in Surakarta that has a very specific character like old cities in Europe, namely physically the area is an enclave with three layers of main roads, neighborhood roads and small alleys (alleys). In this area, the Laweyan batik merchants lived and worked in the batik industry. They have a high position in Surakarta society, but not as a servant in the karaton, so has no obligation to follow the order of life of the nobility, including in the form of his residential building. The lifestyle influenced the design of the house, which tried to follow the traditional Javanese order but was transformed with new forms, especially in the use of building materials that adapted the development of building technology at that time. The purpose of writing is to study the Laweyan batik merchant's house based on the periodization of its construction. The method used is descriptive analytic by conducting observations, interviews, measuring buildings and the environment that is used as a sample. Samples were taken based on the owner's ability to accept researchers due to the pandemic. The results achieved can structure the transformation of form, character, style, and spatial planning based on the period 1800-1900, 1900-1945, 1945-2000, in the form of crosses and incorporation of the typical building characters of the Laweyan merchants can add to the repertoire of architectural wealth in Indonesia.